Gender Stereotypes Against Career Women in the Modern Era (Case Study in Tuban Regency) - Ika Romadhona, Diah Ayu; Kumalasari, Luluk Dwi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
Gender issues and the role of career women in the modern era are pressing topics, given that the average global gender gap remains high and hinders women's professional advancement. This study focuses on the dynamics in non-metropolitan areas, particularly in Kerek District, Tuban Regency, where a contradiction exists between the increase in women's workforce participation and the strength of local gender stereotypes. This study uses a descriptive qualitative approach, with data collected through observation, interviews, and document analysis of five informants, all career women and men aged 20-30 years. The results show that men remain the primary decision-makers, while women are expected to prioritize their household roles over their careers. This situation creates a double burden because household responsibilities are not shared, even though women are working. In addition, despite having personal income, women still have very little control over decisions about allocating household resources. Overall, these findings show that gender stereotypes structurally perpetuate subordination and have a significant regressive impact on women's career advancement. This study provides new insights into how local cultural values influence women's professional opportunities